Determinantes relacionados à institucionalização de idosos : estudo caso-controle - Lini, Ezequiel Vitório (2015)
The elderly institutionalization process has grown in our country, so much that the researches has warned that soon the demand will be greater than the supply of beds. This study aimed to identify the factors that predispose the referral of elderly to homes for the aged. Therefore, it was decided to conduct a study of cases and controls. In all, 387 individuals aged ≥ 60 years old were interviewed. The cases (n= 191) were represented by elderly people living in homes for aged in the city of Passo Fundo, RS who authorized the research in the year 2014. The controls (n = 196) individuals aged ≥ 60 years old of age in the urban area of the municipality. In the comparison between groups were analyzed using chi-squared tests of Pearson and the logistic regression model in the adjusted analysis, with effects expressed in oddsratio with a 95% confidence interval. For entry in the multiple model were considered variables with p ≤ 0.20. After multivariate analysis, remained as risk factors for institutionalization: no partner (single, separated, widowed) (OR = 9.7), do not have children (OR = 4.0), symptoms suggestive of dementia present (OR =11.4) and have dependence for basic activities of daily living (OR=10.9). These results instigate discussions on the institutionalization of reasons given so far by the international literature. Prevention measures to modifiable factors should be prioritized and greater incentive to maintain the domestic care, whether formal or informal